2021
DOI: 10.1038/s41598-021-83358-y
|View full text |Cite|
|
Sign up to set email alerts
|

Dissociating implicit and explicit ensemble representations reveals the limits of visual perception and the richness of behavior

Abstract: Our senses provide us with a rich experience of a detailed visual world, yet the empirical results seem to suggest severe limitations on our ability to perceive and remember. In recent attempts to reconcile the contradiction between what is experienced and what can be reported, it has been argued that the visual world is condensed to a set of summary statistics, explaining both the rich experience and the sparse reports. Here, we show that explicit reports of summary statistics underestimate the richness of en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 52 publications
1
25
0
Order By: Relevance
“…In a recent paper, we studied the effect of distractors upon perceptual decisions about the attended items (targets) during visual search for an oddly oriented line among distractors ( Rafiei, Hansmann-Roth, Whitney, Kristjánsson, & Chetverikov, 2021 ). In visual search, observers can surprisingly quickly learn the probability distributions of distractor sets ( Chetverikov, Campana & Kristjánsson, 2016 ; Chetverikov, Campana & Kristjánsson, 2017a ; Chetverikov, Campana & Kristjánsson, 2017b ; Chetverikov, Campana & Kristjánsson, 2017c ; Chetverikov, Campana & Kristjánsson, 2017d ; Chetverikov, Campana & Kristjánsson, 2020a ; Hansmann-Roth, Chetverikov, & Kristjánsson, 2019 ; Hansmann-Roth, Kristjánsson, & Chetverikov, 2020a ; Hansmann-Roth, Kristjánsson, Whitney, & Chetverikov, 2021 ; Tanrıkulu, Chetverikov & Kristjánsson, 2020 ). They can learn which distractor features are more probable than others in surprising detail, and, importantly, unlike the items typically used in serial dependence studies, observers learn to ignore them.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent paper, we studied the effect of distractors upon perceptual decisions about the attended items (targets) during visual search for an oddly oriented line among distractors ( Rafiei, Hansmann-Roth, Whitney, Kristjánsson, & Chetverikov, 2021 ). In visual search, observers can surprisingly quickly learn the probability distributions of distractor sets ( Chetverikov, Campana & Kristjánsson, 2016 ; Chetverikov, Campana & Kristjánsson, 2017a ; Chetverikov, Campana & Kristjánsson, 2017b ; Chetverikov, Campana & Kristjánsson, 2017c ; Chetverikov, Campana & Kristjánsson, 2017d ; Chetverikov, Campana & Kristjánsson, 2020a ; Hansmann-Roth, Chetverikov, & Kristjánsson, 2019 ; Hansmann-Roth, Kristjánsson, & Chetverikov, 2020a ; Hansmann-Roth, Kristjánsson, Whitney, & Chetverikov, 2021 ; Tanrıkulu, Chetverikov & Kristjánsson, 2020 ). They can learn which distractor features are more probable than others in surprising detail, and, importantly, unlike the items typically used in serial dependence studies, observers learn to ignore them.…”
Section: Introductionmentioning
confidence: 99%
“…Extracting statistical regularities from a scene is a central capacity of the human visual system (e.g., Bar, 2004;Oliva and Torralba, 2007;Chetverikov et al, 2016;Hansmann-Roth et al, 2021). For example, if a searched-for target is repeatedly encountered in an invariant arrangement of distractor elements, observers can learn these configurations and use them to expedite search -an effect termed "contextual cueing" (Chun and Jiang, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…First, regarding efficiency, more work is needed to understand individual differences in the face of effortless processing. For instance, whereas organizationalbehavior work has found individual differences in the ability to extract group-emotion information (Sanchez-Burks et al, 2016), ensemble-coding work has found that efficient processing of group emotion happens both outside of humans' awareness and accurately (Haberman & Whitney, 2010;Hansmann-Roth et al, 2021). Thus, it is unclear how such processing contributes to individual differences or whether later-stage processing may be interfering (e.g., Haberman, Brady, & Alvarez, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Third, active debates within the ensemble-coding literature consider to what degree people perception is truly automatic, as well as to what degree such perception relies on truly distinct processing mechanisms compared with those involved in individual person perception (Hansmann-Roth et al, 2021;Neumann et al, 2017;Whitney & Yamanashi Leib, 2018;ZeeAbrahamsen & Haberman, 2018). This question of automaticity has long been an issue within social-vision research and psychological research more broadly (Bargh, 1994).…”
Section: Discussionmentioning
confidence: 99%